Trophic interactions within the microbial food web in a tropical floodplain lake (Laguna Bufeos, Bolivia) - Rejas, Danny (2005)
Whether the primary role of bacterioplankton is to act as “remineralizers” of nutrients or as direct nutritional source for higher trophic levels will depend on factors controlling their production and abundance. In tropical lakes, low nutrient concentration is probably the main factor limiting bacterial growth, while grazing by microzooplankton is generally assumed to be the main loss factor for bacteria. Bottom-up and top-down regulation of microbial abundance was studied in six nutrient limitation and dilution gradient-size fractionation in situ experiments. Bacteria, heterotrophic nanoflagellates (HNF), ciliates and rotifers showed relatively low densities. Predation losses of HNF and ciliates accounted for a major part of their daily production, suggesting a top-down regulation of protistan populations by rotifers. Phosphorus was found to be strongly limiting for bacterial growth, whereas no response to enrichment with Nitrogen or DOC was detected. HNF were the major grazers on bacteria (g=0.43 d-1), the grazing coefficient increased when ciliates were added (g= 0.80 d-1) but decreased when rotifers were added (g= 0.23 d-1) probably due to nutrient recycling or top-down control of HNF and ciliates by rotifers.